Antifungal effects of indolicidin-conjugated gold nanoparticles against fluconazole-resistant strains of Candida albicans isolated from patients with burn infection - Rahimi H (Dove Medical Press, 2019)
Hossein Rahimi,1 Shahla Roudbarmohammadi,1 Hamid Delavari H,2 Maryam Roudbary31Department of Medical Mycology, Faculty of Medical Sciences, Tarbiat Modares University, Tehran, Iran; 2Department of Materials Engineering, Faculty of Engineering, Tarbiat Modares University, Tehran, Iran; 3Department of Medical Mycology and Parasitology, School of Medicine, Iran University of Medical Sciences, Tehran, IranBackground: Candida albicans as an opportunistic fungus is one of the most important causes of late-onset morbidity and mortality in patients with major burns and severely impaired immune system. In recent years, the emergence of resistance to opportunistic fungi and toxicity of antimicrobial drugs make it necessary to develop new drugs.Methods: In the present study, we investigated anticandidal effects of indolicidin, as a representative of host defense peptide, conjugated with gold nanoparticles in fluconazole-resistant clinical isolates of C. albicans. After characterizing the conjugation of indolicidin using biophysical methodologies, the cytotoxicity and hemolytic activity of the nanocomplex were examined. In addition, the expression level of ERG11, responsible for antifungal resistance, and the immunomodulatory effect of peptide-nanomaterial conjugates were assessed.Results: Our data indicated that the nanocomplex was nontoxic for the fibroblast cells and erythrocytes. Treatment with the nanocomplex significantly reduced the expression levels of the ERG11 gene in fluconazole-resistant C. albicans isolates and the iNOS gene in macrophages.Conclusion: The study data provides a chance to develop innovative therapies for the treatment of C. albicans burn infections. However, further investigation is required to examine the efficiency of the nanocomplex.Keywords: burn infection, Candida albicans, indolicidin, gold nanoparticles, antimicrobial peptides